Juridic Review On Civil Decisions Which Was Not Executed Because Of Resistance In The Tobelo State Court" (Judiction Analysis Number 11/Pdt.G/2011/Pn.Tbl - Donylisan F. Romkeny; Rusdin Alauddin; Faissal Malik (LEGAL BRIEF, 2022)
This study is to find out the legal actions taken in the execution of the Tobelo District Court and what are the causes of the non-execution of the object in case Number 11/Pdt.G/2011/PN.TBL which has permanent legal force (inkracht). This research is a normative legal research, namely research that focuses on examining the decision of the Tobelo District Court regarding claims for land ownership without rights and why the decisions of the Tobelo court judges who already have legal force are still hampered in the execution process. The source of data used in this study is secondary data, namely data obtained from library research and documents, which are the results of research and processing of others, which are already available in the form of books or documents that are usually provided in libraries, or privately owned. In legal research, secondary data includes primary legal materials, secondary legal materials, and tertiary legal materials. Based on the results of the research conducted, it can be concluded that this decision cannot be executed due to resistance to the object by third parties and the defendants / defendants. There were also executions that were hampered because when the execution confiscation was about to be placed on the object of the case, it turned out that the object of the case had changed hands to a third party due to the National Land Agency (BPN) continuing to process the transfer of names or the issuance of a new certificate on the object of the dispute. Upon the request for execution, a third party who also feels that they have the right to the object of the dispute then submits another rebuttal or resistance to the execution.